NJSS 2021
DOI: 10.36265/njss.2021.310306
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of soil and nutrient loss due to yam harvesting: A case study in two local government areas in Benue state, Nigeria.

Abstract: Soil loss due to crop harvesting is a recognized erosion process which has significantly contributed to soil degradation. Despite its significance, soil loss due to crop harvesting has been given little attention in Benue state and Nigeria at large. This is evident in the paucity of information on soil loss due to crop harvesting in Nigeria. Therefore a field experiment was conducted to quantify soil and nutrient loss due to yam harvesting in two local government areas (Kwande and Ushongo) of Benue state and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Dada et al (2016) also observed that soil bulk density in addition to soil texture has significant effects on soil loss. Similarly, Samson and Ityavnongo (2021) in an experiment, reported a significant relationship between soil texture and soil loss due to yam harvesting. However, in our study, soil properties such as bulk density and soil texture had no relationship with soil loss.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Dada et al (2016) also observed that soil bulk density in addition to soil texture has significant effects on soil loss. Similarly, Samson and Ityavnongo (2021) in an experiment, reported a significant relationship between soil texture and soil loss due to yam harvesting. However, in our study, soil properties such as bulk density and soil texture had no relationship with soil loss.…”
Section: Discussionmentioning
confidence: 82%
“…Other studies have reported soil properties such as bulk density, soil structure, and texture to be critical factors controlling soil loss (Ruysschaert et al, 2007b;Dada et al, 2016;Oshunsanya et al, 2018;Parlak et al, 2021 andItyavnongo, 2021). For example, Oshunsanya et al (2018) reported soil bulk density negatively related to soil loss due to yam harvesting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations